Analisis Pemahaman Konsep Matematika Siswa Smait Nurul Fajri dalam Menyelesaikan Soal Higher Order Thinking Skills (Hots) - Nurul Aisyah; Supardi Uki Sajiman (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the understanding of high school students in solving high, medium, and low category HOTS (Higher Order Thinking Skills) problems and to explore the students' responses in solving problems related to the material of SPLTV (System of Linear Equations with Three Variables). This research is qualitative in nature, using a descriptive method. The subject selection technique used purposive sampling, involving three students from class X IPA/IPS SMAIT Nurul Fajri, with a total of 19 students. The data collection techniques included written tests on mathematical concept understanding using HOTS, interviews, and documentation. Based on the research results, it was found that the students' understanding of mathematical concepts in solving HOTS problems varied. The subject NF-17, with high ability, was able to answer well, including restating the concepts studied in problems 1, 2, and 4, classifying objects based on concepts, applying concepts algorithmically, relating various mathematical concepts internally or externally, providing examples or counterexamples, and presenting concepts in various representations in problems 1, 3, and 4. The subject NF-18, with medium ability, showed more limited results. Although able to restate concepts in problem 4, this subject could only classify objects based on concepts and apply concepts algorithmically in problems 1 and 4. This subject could only provide examples or counterexamples in problem 1. The subject NF-10, with low ability, was only able to restate concepts studied in problem 1 and did not show more in-depth understanding in other problems. These findings indicate variations in students' understanding of mathematical concepts in the SPLTV material.